Challenges and Development in Suzhou Laboratory Animal Industry Over the Past Five Decades - ZHAO Lijuan; XIAO Chunlan; SHENG Yajie; LU Xi; ZHOU Zhengyu (Shiyan dongwu yu bijiao yixue)
Since the 1970s, the laboratory animal industry in Suzhou has gone through five stages: its inception, emergence, growth, transformation, and scaling up. It began with the manufacturing of caging equipment for laboratory animals, initially by imitation and later through independent innovation. The industry evolved from sporadic factories to clustered enterprises, gradually growing and opening up the export market for caging equipment. In the 21st century, with industrial upgrading and transformation, purification systems and related products began to develop, and industry organizations emerged. As China has modernized, the rise of automation and intelligent production has led to technological innovation in enterprises and the emergence of various outsourcing services in the laboratory animal industry, driving the large-scale development of the industrial chain. After nearly half a century of growth, the laboratory animal industry in Suzhou has formed a complete industrial chain, including the production of laboratory animals, caging equipment, feed and bedding materials, design and construction of laboratory animal facilities, quality testing of laboratory animals and environments, and animal experimentation services. Laboratory animal breeding equipment, the core of the industry, has reached the level of developed countries, and the industry's scale and influence are unmatched in China. Since the 21st century, biopharmaceuticals have become the "No.1 industry" in the development of Suzhou. With government support, the guidance of the local economy, and the assistance from universities and research institutes, the animal experiment outsourcing industry has begun to cluster in Suzhou. The continuous influx of CROs has driven the construction of large-scale laboratory animal facilities, and key research projects have been initiated, significantly enhancing the industry's R&D capabilities. The Suzhou laboratory animal industry has quickly expanded alongside the "No. 1 industry," creating a unique "Suzhou Path" for laboratory animals. Over nearly fifty years, the laboratory animal industry in Suzhou has been essential to the rapid development of the biopharmaceutical industry in Suzhou and China.